Interplay between bacterial virulence and plant innate immunity in Ppseudomonas-arabidopsis interactions - Li, Xinyan (Kansas State University, 2006)
Plants activate innate immune responses or innate immunity upon pathogen infection. There are two types of plant innate immunity: PAMP-triggered innate immunity (PTI) and effector-triggered innate immunity (ETI). The molecular basis for ETI has been well documented. However, the study on PTI and its interplay with pathogen virulence is in its infancy. My research focuses on the interplay between PTI and bacterial virulence in Pseudomonas-Arabidopsis interactions. NHO1, a gene required for nonhost resistance to Pseudomonas syringae, encodes for the 3-glycerol kinase in Arabidopsis genome. NHO1 functions, at least in part, by depriving glycerol from nonhost bacteria cells. NHO1 is induced by a well-known bacteria PAMP flg22. The induction of NHO1 correlates well with the resistance against Pseudomonas syringae pv. tabaci because a mutant strain of P. s. pv. tabaci deficient in NHO1 induction gains partial virulence on Arabidopsis plants. P. s. pv. tomato strain DC3000 induces transient NHO1 expression that is suppressed in a type III secrection system-dependent manner. Using protoplast assay, nine DC3000 effectors that are able to suppress NHO1 were identified. One of them, HopAI1, induces leaf chlorosis and helps nonpathogenic bacterial growth when expressed in Arabidopsis plants, suggesting that HopAI1 has virulence activity in planta. To study AvrB virulence activity in Arabidopsis plants, one mutant compromised in AvrB-specific RAR2.6 induction has been characterized in detail. rrb3 is more susceptible to a nonhost bacteria P. s. pv. tabaci strain 6505, a virulent bacteria P. s. pv. tomato strain DC3000 and an avirulent bacteria strain DC3000 (avrB). The mutant allele rrb3 carries a point mutation at the end of RAR1 CHORD II domain. RRB3 (RAR1), together with NDR1, is involved in the type II nonhost resistance to P. s. pv. tabaci but not in the type I nonhost resistance to P. s. pv. phaseolicola. RAR1 participates in basal resistance against DC3000 by antagonizing COI1 activity. AvrB targets RAR1 to trigger AvrB-dependent leaf chlorosis and enhanced bacterial growth. The AvrB-dependent enhanced bacterial growth but not leaf chlorosis requires COI1, suggesting that AvrB targets JA signaling pathway to promote parasitism.
Keywords: Plant innate immunity; Pseudomonas syringae; Bacterial virulence; Arabidopsis; Agriculture, Plant Pathology (0480)